2010
DOI: 10.21236/ada531913
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bacterial and Viral Bio-Warfare Agents in Disinfected Waters

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathenng and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense. Washington Headquarters Services. Directorate for Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study evaluating the survival of Y. pestis in formulated tap water with chlorine, revealed that common chlorination of tap water is effective at killing Y. pestis [3,4]. In consequence, rigorous cleaning of either skin or wound with lots of water and soap (mechanical purification) followed by 2 min wash using skin antiseptic or 0.2% peracetic acid should be effective.…”
Section: Skin/wound Disinfectionmentioning
confidence: 99%
“…A study evaluating the survival of Y. pestis in formulated tap water with chlorine, revealed that common chlorination of tap water is effective at killing Y. pestis [3,4]. In consequence, rigorous cleaning of either skin or wound with lots of water and soap (mechanical purification) followed by 2 min wash using skin antiseptic or 0.2% peracetic acid should be effective.…”
Section: Skin/wound Disinfectionmentioning
confidence: 99%